Studying the Effect of Volume Fraction of Glass Fibers on the Thermal Conductivity of the Polymer Composite Materials - Hamza, Mohammed Sellab (Al-Khwarizmi Engineering Journal, 2019)
In this study the effect of fiber volume fraction of the glass fiber on the thermal conductivity of the polymer composite material was studied. Different fiber volume fraction of glass fibers were used (3%, 6%, 9%, 12%, and 15%). Specimens were made from polyester which reinforced with glass fibers .The fibers had two arrangements according to the direction of the thermal flow. In the first arrangement the fibers were parallel to the direction of the thermal flow, while the second arrangement was perpendicular; Lee's disk method was used for testing the specimens. The experimental results proved that the values of the thermal conductivity of the specimens was higher when the fibers arranged in parallel direction than that when the fibers arranged in the perpendicular direction. The percentage of increasing of experimental thermal conductivity was 96.91% for parallel arrangement and 13.33% for perpendicular arrangement comparison with its original value before the using of glass fibers.Also the experimental results indicated that the thermal conductivity increases with the increasing of the fiber volume fraction. Minimum value was (0.172 W/m.°C) for perpendicular arrangement at fiber volume fraction 3% and maximum value was (0.327 W/m.°C) for parallel arrangement at fiber volume fraction 15%.